2004
DOI: 10.1111/j.1365-2796.2004.01380.x
|View full text |Cite
|
Sign up to set email alerts
|

Mild cognitive impairment – beyond controversies, towards a consensus: report of the International Working Group on Mild Cognitive Impairment

Abstract: . The First Key Symposium was held in Stockholm, Sweden, 2–5 September 2003. The aim of the symposium was to integrate clinical and epidemiological perspectives on the topic of Mild Cognitive Impairment (MCI). A multidisciplinary, international group of experts discussed the current status and future directions of MCI, with regard to clinical presentation, cognitive and functional assessment, and the role of neuroimaging, biomarkers and genetics. Agreement on new perspectives, as well as recommendations for ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

50
3,678
3
143

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 4,253 publications
(3,874 citation statements)
references
References 0 publications
50
3,678
3
143
Order By: Relevance
“…We considered as cases all the participants who met the revised Mayo Clinic criteria for MCI: (1) cognitive concern expressed by a physician, informant, participant, or nurse; (2) cognitive impairment in one or more domains (executive function, memory, language, or visuospatial); (3) normal functional activities; and (4) not demented 2, 3 . Subjects with MCI could have a Clinical Dementia Rating Scale score of 0 or 0.5; however, the final diagnosis of MCI was not based exclusively on the clinical dementia rating, but rather on all available data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We considered as cases all the participants who met the revised Mayo Clinic criteria for MCI: (1) cognitive concern expressed by a physician, informant, participant, or nurse; (2) cognitive impairment in one or more domains (executive function, memory, language, or visuospatial); (3) normal functional activities; and (4) not demented 2, 3 . Subjects with MCI could have a Clinical Dementia Rating Scale score of 0 or 0.5; however, the final diagnosis of MCI was not based exclusively on the clinical dementia rating, but rather on all available data.…”
Section: Methodsmentioning
confidence: 99%
“…The reader is referred elsewhere for a detailed discussion of MCI 2, 3 . Subjects with MCI constitute a high risk group because they develop dementia at a rate of 10% to 15% per year compared with 1% to 2% per year in the general population 4 .…”
mentioning
confidence: 99%
“…Mild cognitive impairment (MCI) often represents an early transition stage between normal functioning and dementia and refers to cognitive impairment greater than expected for age but without meeting criteria for a dementia diagnosis (Winblad et al, 2004). MCI would be expected to have an insidious onset as well.…”
Section: Introductionmentioning
confidence: 99%
“…This state is termed amnestic MCI (Winblad et al, 2004) when other nonmemory cognitive functions are essentially preserved, although mild decline may be observed in these other areas (Devanand et al, 1997;Grundman et al, 2004;Twamley et al, 2006). In their study, Devanand and colleagues found that low scores on delayed recall, category naming for animals, and the Wechsler Adult Intelligence Scale-Revised (WAIS-R; Wechsler, 1981) Digit Symbol, Picture Arrangement, and Block Design subtests were predictive of diagnosis of dementia 2 to 3 years later.…”
Section: Introductionmentioning
confidence: 99%
“…treatment with acetylcholinesterase inhibitors (AChEI) or ginkgo biloba). To date, randomized controlled trials
Box 1.General Criteria for MCI (Modified after [3])●  Diagnosis based on clinical judgement●  Report of cognitive decline by the patient and / or an informant Cognitive impairment in one or more domains (e.g. memory, attention, language, visuospatial skills, perceptual speed or executive functioning).
…”
Section: Introductionmentioning
confidence: 99%